ON THE WISDOM OF RETICENCE AT THE CROSSING OF SPIRITUAL BORDERS - Clooney, Francis X. (The Way / Supplement, 2002)
When preaching out of a knowledge of another religion, it is often wise to say less than full explanation might demand, leaving for the individual listener the freedom to meet Christ anew through experiencing another tradition